A study for categorizing relations between headword and aliases. Issue 1 (18th October 2019) - Kim, Jiyoun; Koo, Youngeun; Zhu, Yongjun
ABSTRACT: In this study, we propose a method of categorizing relations between a headword and its aliases using Korean Wikipedia data. We propose orthographically similar types and orthographically different types. Orthographically similar types are divided into 5 types: Word space, Pronunciation difference, Omission, Abbreviation, and Word order change while different types are also classified into 4 types: Foreign word, Acronym, Paraphrased expression and Call name. We show examples to verify the proposed method.